Resources
Testimonials
Plans
Sign in
Sign up
Resources
Testimonials
Plans
AI tutor
Welcome to Bytelearn!
Let’s check out your problem:
lim
n
→
∞
(
a
−
1
+
b
n
a
)
n
\lim _{n \rightarrow \infty}\left(\frac{a-1+\sqrt[n]{b}}{a}\right)^{n}
lim
n
→
∞
(
a
a
−
1
+
n
b
)
n
View step-by-step help
Home
Math Problems
Precalculus
Evaluate rational exponents
Full solution
Q.
lim
n
→
∞
(
a
−
1
+
b
n
a
)
n
\lim _{n \rightarrow \infty}\left(\frac{a-1+\sqrt[n]{b}}{a}\right)^{n}
lim
n
→
∞
(
a
a
−
1
+
n
b
)
n
Rewrite Limit Expression:
First, let's rewrite the limit expression to make it clearer.
lim
n
→
∞
(
a
−
1
+
b
n
a
)
n
\lim_{n \rightarrow \infty}\left(\frac{a-1+\sqrt[n]{b}}{a}\right)^{n}
lim
n
→
∞
(
a
a
−
1
+
n
b
)
n
Rewrite Inside Parentheses:
Notice that the expression inside the parentheses can be rewritten as
1
+
(
b
n
−
1
)
/
a
1 + (\sqrt[n]{b} - 1)/a
1
+
(
n
b
−
1
)
/
a
. So, we have
lim
n
→
∞
(
1
+
(
b
n
−
1
)
/
a
)
n
\lim_{n \to \infty}(1 + (\sqrt[n]{b} - 1)/a)^{n}
lim
n
→
∞
(
1
+
(
n
b
−
1
)
/
a
)
n
Use Limit Property:
Now, let's use the fact that
lim
n
→
∞
(
1
+
x
n
)
n
=
e
x
\lim_{n \to \infty}\left(1 + \frac{x}{n}\right)^n = e^x
lim
n
→
∞
(
1
+
n
x
)
n
=
e
x
when
n
n
n
approaches infinity.
\newline
Here,
x
=
b
n
−
1
a
x = \frac{\sqrt[n]{b} - 1}{a}
x
=
a
n
b
−
1
.
Determine
x
x
x
Value:
As
n
n
n
approaches infinity,
b
n
\sqrt[n]{b}
n
b
approaches
0
0
0
, so
(
b
n
−
1
)
/
a
(\sqrt[n]{b} - 1)/a
(
n
b
−
1
)
/
a
approaches
−
1
/
a
-1/a
−
1/
a
.
Calculate Final Limit:
Therefore, the limit becomes
e
(
−
1
/
a
)
e^{(-1/a)}
e
(
−
1/
a
)
.
Final Answer:
So, the final answer is
e
(
−
1
/
a
)
e^{(-1/a)}
e
(
−
1/
a
)
.
More problems from Evaluate rational exponents
Question
f
(
x
)
=
6
x
+
5
2
−
14
+
5
x
f(x)=\frac{6 x+5}{2-\sqrt{14+5 x}}
f
(
x
)
=
2
−
14
+
5
x
6
x
+
5
\newline
We want to find
lim
x
→
−
2
f
(
x
)
\lim _{x \rightarrow-2} f(x)
lim
x
→
−
2
f
(
x
)
.
\newline
What happens when we use direct substitution?
\newline
Choose
1
1
1
answer:
\newline
(A) The limit exists, and we found it!
\newline
(B) The limit doesn't exist (probably an asymptote).
\newline
(C) The result is indeterminate.
Get tutor help
Posted 1 year ago
Question
Let
x
4
+
y
2
=
17
x^{4}+y^{2}=17
x
4
+
y
2
=
17
.
\newline
What is the value of
d
2
y
d
x
2
\frac{d^{2} y}{d x^{2}}
d
x
2
d
2
y
at the point
(
−
2
,
1
)
(-2,1)
(
−
2
,
1
)
?
\newline
Give an exact number.
Get tutor help
Posted 1 year ago
Question
What is the area of the region bound by the graphs of
f
(
x
)
=
x
−
2
,
g
(
x
)
=
14
−
x
f(x)=\sqrt{x-2}, g(x)=14-x
f
(
x
)
=
x
−
2
,
g
(
x
)
=
14
−
x
, and
x
=
2
x=2
x
=
2
?
\newline
Choose
1
1
1
answer:
\newline
(A)
19
6
\frac{19}{6}
6
19
\newline
(B)
99
2
\frac{99}{2}
2
99
\newline
(C)
151
2
\frac{151}{2}
2
151
\newline
(D)
45
2
\frac{45}{2}
2
45
Get tutor help
Posted 1 year ago
Question
Let
g
(
x
)
=
x
4
3
g(x)=x^{\frac{4}{3}}
g
(
x
)
=
x
3
4
.
\newline
g
′
(
27
)
=
g^{\prime}(27)=
g
′
(
27
)
=
Get tutor help
Posted 1 year ago
Question
Simplify
ln
(
1
e
)
\ln \left(\frac{1}{\sqrt{e}}\right)
ln
(
e
1
)
\newline
Answer:
Get tutor help
Posted 1 year ago
Question
Simplify
ln
(
1
e
)
\ln \left(\frac{1}{e}\right)
ln
(
e
1
)
\newline
Answer:
Get tutor help
Posted 1 year ago
Question
y
=
(
sin
−
1
(
5
x
2
)
)
3
y=(\sin^{-1}(5x^{2}))^{3}
y
=
(
sin
−
1
(
5
x
2
)
)
3
Get tutor help
Posted 1 year ago
Question
(
10
x
3
−
5
x
2
−
6
x
)
÷
(
2
x
2
)
\left(10x^{3}-5x^{2}-6x\right)\div\left(2x^{2}\right)
(
10
x
3
−
5
x
2
−
6
x
)
÷
(
2
x
2
)
Get tutor help
Posted 1 year ago
Question
y
=
cos
4
x
sin
4
x
y=\cos^{4}x\sin^{4}x
y
=
cos
4
x
sin
4
x
Get tutor help
Posted 1 year ago
Question
3
5
−
3
10
\frac{3}{5}-\frac{3}{10}
5
3
−
10
3
Get tutor help
Posted 1 year ago
Related topics
Algebra - Order of Operations
Algebra - Distributive Property
`X` and `Y` Axes
Geometry - Scalene Triangle
Common Multiple
Geometry - Quadrant